2003
DOI: 10.1085/jgp.200308812
|View full text |Cite
|
Sign up to set email alerts
|

Saxitoxin Is a Gating Modifier of hERG K+ Channels

Abstract: Potassium (K+) channels mediate numerous electrical events in excitable cells, including cellular membrane potential repolarization. The hERG K+ channel plays an important role in myocardial repolarization, and inhibition of these K+ channels is associated with long QT syndromes that can cause fatal cardiac arrhythmias. In this study, we identify saxitoxin (STX) as a hERG channel modifier and investigate the mechanism using heterologous expression of the recombinant channel in HEK293 cells. In the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 42 publications
0
80
0
3
Order By: Relevance
“…Anatoxin-a(s) irreversibly inhibits acetylcholinesterase (AChE) in the neuro-muscular junctions in the peripheral nervous system only. Saxitoxins (STXs) are a family of more than 30 natural alkaloids, synthesized by both freshwater cyanobacteria and by marine dinoflagellates by similar processes [51]: they block Na-channels in neuronal cells [52] and Ca ++ and K + channels in cardiac cells, thus preventing the propagation of electrical transmission within the peripheral nerves and skeletal or cardiac muscles [53]. Based on the kind of intoxication, they are also called Paralytic Shellfish Poisoning (PSP).…”
Section: Toxicological Profiles Of Cyanotoxinsmentioning
confidence: 99%
“…Anatoxin-a(s) irreversibly inhibits acetylcholinesterase (AChE) in the neuro-muscular junctions in the peripheral nervous system only. Saxitoxins (STXs) are a family of more than 30 natural alkaloids, synthesized by both freshwater cyanobacteria and by marine dinoflagellates by similar processes [51]: they block Na-channels in neuronal cells [52] and Ca ++ and K + channels in cardiac cells, thus preventing the propagation of electrical transmission within the peripheral nerves and skeletal or cardiac muscles [53]. Based on the kind of intoxication, they are also called Paralytic Shellfish Poisoning (PSP).…”
Section: Toxicological Profiles Of Cyanotoxinsmentioning
confidence: 99%
“…PSTs affect vertebrate nerve function by reversibly blocking voltage-gated ion channels, primarily Na + (Llewellyn, 2006), but also K + and Ca 2+ channels are affected (Kao, 1986, Wang et al, 2003, Su et al, 2004. Ion channel blockage leads to inhibition of neuronal signal transduction, the extent of which is directly dependent on PST concentration.…”
mentioning
confidence: 99%
“…There are two major classes of toxins, the pore-blocking [29,47] and the gatingmodifying [48,49], which have been widely used to determine K + channel structure and function. The interaction between toxins and the channel was studied by the two-electrode voltage-clamp recording techniques by many researchers.…”
Section: Discussionmentioning
confidence: 99%
“…The last is sensitive to changes in ion concentration [51] and to tetraethyl ammonium (known as external pore blocker) as well [52]. On the other hand, gating-modifier toxins bind to the voltage-sensor domain [48,49]. It has been found that ErgTx1 binds to the outer vestibule of hERG [26,27] like other pore blocking toxins and sensitive to tetraethyl ammonium [28].…”
Section: Discussionmentioning
confidence: 99%